Freedom to think aloud - Leighton, Jacqueline P. (Frontiers in Education, 2024)
The collection of think aloud data on critical thinking tasks requires participants, many of whom are postsecondary students, to engage with real-life and potentially controversial topics. Accuracy of verbal reports can be enhanced with clear instructions and by minimizing distracting events. For example, interviewers can minimize external distractions such as ambient noise by holding think aloud sessions in a quiet room. However, internal distractions such as participants’ fears about freely expressing their thoughts about controversial topics may be more difficult for interviewers to address. Although the fear of freely expressing thoughts during think aloud interviews has not been empirically investigated, this needs to change. Large-scale surveys indicate that a sizable portion of postsecondary students report discomfort with expressing their thoughts on some topics. This paper offers a theoretical case for why participants’ fears about voicing thoughts freely and without reprisal during think aloud sessions may not only potentially undermine the truthfulness of verbal reports and validity of inferences, but also the very study of critical thinking. Thus, an empirical case for the freedom to think aloud must be considered.